Multilocus Fragment Typing and Genetic Structure of Cryptosporidium parvum Isolates from Diarrheic Preweaned Calves in Spain - Quílez, Joaquín (American Society for Microbiology, 2011)
A collection of 140 Cryptosporidium parvum isolates previously analyzed by PCR-restriction fragment length polymorphism (PCR-RFLP) and sequence analyses of the small-subunit (SSU) rRNA and 60-kDa glycoprotein (GP60) genes was further characterized by multilocus fragment typing of six minisatellite (MSB and MS5) and microsatellite (ML1, ML2, TP14, and 5B12) loci. Isolates were collected from diarrheic preweaned calves originating from 61 dairy cattle farms in northern Spain. A capillary electrophoresis-based tool combining three different fluorescent tags was used to analyze all six satellites in one capillary. Fragment sizes were adjusted after comparison with sizes obtained by sequence analysis of a selection of isolates for every allele. Size discrepancies at all but the 5B12 locus were found for those isolates that were typed by both techniques, although identical size differences were reported for every allele within each locus. A total of eight alleles were seen at the ML2 marker, which contributed the most to the discriminatory power of the multilocus approach. Multilocus fragment typing clearly improved the discriminatory power of GP60 sequencing, since a total of 59 multilocus subtypes were identified based on the combination of alleles at the six satellite loci, in contrast to the 7 GP60 subtypes previously reported. The majority of farms (38) displayed a unique multilocus subtype, and individual isolates with mixed multilocus subtypes were seen at 22 farms. Bayesian structure analysis based on combined data for both satellite and GP60 loci suggested the presence of two major clusters among the C. parvum isolates from cattle farms in this geographical area.